2022
DOI: 10.1186/s12967-022-03294-x
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in the tumor microenvironment of cholangiocarcinoma: current status and future perspectives

Abstract: Cholangiocarcinoma (CCA) refers to an aggressive malignancy with a high fatality rate and poor prognosis. Globally, the morbidity of CCA is increasing for the past few decades, which has progressed into a disease that gravely endangers human health. Exosomes belong to a class of extracellular vesicles (EVs) with diameters ranging from 40 to 150 nm that can be discharged by all living cells. As communication messengers of the intercellular network, exosomes carry a diverse range of cargoes such as proteins, nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 89 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…According to previous research, TME plays a key role in the development of a variety of human cancers, 99 and exosomes are key components of TME that be isolated from various body fluids and contain specific RNAs, proteins or metabolites. These exosomes have a unique regulatory role in modulating TME.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, TME plays a key role in the development of a variety of human cancers, 99 and exosomes are key components of TME that be isolated from various body fluids and contain specific RNAs, proteins or metabolites. These exosomes have a unique regulatory role in modulating TME.…”
Section: Discussionmentioning
confidence: 99%
“…In the TME, complex intercellular communication occurs between various cell clusters, which jointly promote tumor progression (33). To gain insight into the relationship between TME and tumor cells in BTCs, we inferred the receptor-ligand interactions between them using the iTALK method (Fig.…”
Section: Receptor-ligand Interactions Between Tumor and Tme Cellsmentioning
confidence: 99%
“…Exosomes produced by tumor stem cells have been shown to be essential for tumor development and progression in recent years due to their ability to control TME elements locally or remotely in an autocrine or paracrine manner 15 . According to our study, the connection between CSC-Exos and TME is mainly re ected in the fact that exosomes regulate the growth and metastasis of tumor cells, participate in tumor angiogenesis and have potential value as tumor diagnostics [46][47][48][49] . In addition, it has also been shown that because CSC-Exos deliver key molecules that are responsive to chemotherapy and immunotherapy, they may also contribute to tumor drug resistance and impede effective responses to antitumor immunotherapy, leading to poor clinical outcomes 50,51 .…”
Section: The Hotspots and Frontiersmentioning
confidence: 99%